Saurischian (theropod–sauropod) track assemblages from the Jiaguan Formation in the Sichuan Basin, Southwest China: ichnology and indications to differential track preservation. (16th November 2016) - Xing, Lida; Peng, Guangzhao; Lockley, Martin G.; Ye, Yong; Klein, Hendrik; McCrea, Richard T.; Zhang, Jianping; Persons, W. Scott
Abstract: Saurischian (theropod and sauropod) tracks and trackways from the Jiaguan Formation (Lower Cretaceous) of the Sichuan Basin are exposed as natural casts with associated undertrack or transmitted print casts. The theropod tracks (cf. Eubrontes and Grallator ) were left by differently sized trackmakers. This is a further example for the occurrence of characteristic Lower Jurassic ichnotaxa in the Cretaceous that obviously had a more extended stratigraphic range in East Asia. The sauropod trackway is tentatively assigned to cf. Brontopodus based on imprint morphology and (nearly wide) gauge. The tracks, however, allow a detailed study of their formation and the taphonomic processes under different substrate conditions. Differential preservation and erosion of primary sedimentary structures, and post-burial deformation structures, give insight into a complex preservational history during a low energy phase interrupting the deposition of a sequence of thick high energy sandstones. This is the sixth report of dinosaur tracks from the Jiaguan Formation and the fifteenth report from the Lower Cretaceous of Sichuan Province. Thus, the tetrapod ichnological record in this region is rapidly becoming of major importance for our knowledge of dinosaur faunas in south-western China.